Electron-Vibration Structure of Absorption Spectra of Resazurine - T.N. Sakun; Yu.M. Lopatkin; P.O. Kondratenko (Журнал нано- та електронної фізики)
In the work the experimental and theoretical investigation of the spectral characteristics of a resazurin molecule are carried out. Comparison of results of experimental and theoretical researches has allowed showing, that the spectrum of absorption in the visible region is formed by quantum transitions between electronic states of the molecule, and also by the electron-vibration interaction. In the work the method of reception of theoretical results with the control of molecule symmetry is offered. It has allowed to receive the completely coordinated theoretical and experimental results both by position and by size of the extinction factor and to find out the nature of all quantum transitions and oscillatory frequencies. It is shown, that strips of absorption in the visible region of the spectrum are formed at participation of the totally symmetrical vibrations of the molecule among which the greatest participation stand out vibrations with frequencies in the region of 478 cm – 1, 1467 cm – 1, and also by group of oscillatory frequencies in the region of 1800-2000 cm – 1 which were less than found theoretically for the basic state of the molecule because the degree of loosening of the bonds that responsible for specified vibrations, increases at excitation of the molecule.